Multiple Avalons: Place Naming Practices and a Mythical Arthurian Island - Philip Hayward (Island Studies Journal, 2022)
The island of Avalon features in British Arthurian legendry. While its very existence — let alone any actual location it may have had — is contentious, it is now commonly associated with Glastonbury, in the English county of Somerset. Illustrating its enduring appeal, Avalon’s name has also been affixed to a number of international locations over the last 500 years. There have been various motivations for such place naming, including religious beliefs, personal associations, and various types of boosterism, all attempting to imbue New World locales with Old World mystique through nomenclative association. This article surveys the deployment of the concept of Avalon through anglophonic colonial and postcolonial place naming and examines the varying ways in which the name has been applied in different national and local contexts. Its survey reveals direct references to the legendary isle in place naming between the 17th and early 20th centuries and, generally, more weakly associative and/or arbitrary connections over the last century. The study contributes to the expansion of island studies by analysing how a mythical island has been projected onto various non-island locations, and contributes to the development of toponymic studies by examining multiple uses of a single place name.